Are Emotions Psychological Constructions?. Issue 4 (December 2019) - Kurth, Charlie
Abstract : According to psychological constructivism, emotions result from projecting folk emotion concepts onto felt affective episodes. While constructivists acknowledge there is a biological dimension to emotion, they deny that emotions are (or involve) affect programs. So they also deny emotions are natural kinds. However, the essential role that constructivism gives to felt experience and folk concepts leads to an account that is extensionally inadequate and functionally inaccurate. Moreover, biologically oriented proposals that reject these commitments are not similarly encumbered. Recognizing this has two implications: biological mechanisms are more central to emotion than constructivism allows, and the conclusion that emotions are not natural kinds is premature.